ANALISIS PENGARUH CITRA MEREK, NILAI PELANGGAN, DAN KEPUASAN PELANGGAN TERHADAP MINAT BELI ULANG PELANGGAN TUPPERWARE DI MAGELANG - Oceani, Oceani; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2017)
In mid 2015 the waste management in Magelang is already included in the emergency garbage so it is recommended to reduce the use of plastics by using a container that is not directly in the exhaust. However, Tupperware experiencing fluctuating sales results and a decline in sales in a row in 2014 and 2015. The decline in sales can occur because of a lack of customer interest to repurchase the Tupperware brand products. This research aims to find the effect of brand image, customer perceived value and customer satisfaction to the repurchase intentions. It is also to find the effect of customer satisfaction in mediating the repurchase intentions. The research was conducted on consumers who have made purchases of Tupperware products at least twice in the last three months in the territory of Magelang. The model was tested based on the questionnaire data on 100 respondents were analyzed using multiple regression analysis, path analysis, and sobel test. The results showed that both independent variables (brand image and customer perceived value) positive effect on the variable's customers satisfaction and also on variable repurchase intentions. Similarly, the variable customer satisfaction as an intervening variable also has a positive effect on the variable repurchase intentions. Customer Perceived value is the variable that has the most influence on the repurchase intentions.